2011
DOI: 10.1111/j.1750-3841.2010.02015.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Degradation in a Model Apple Juice System and in Apple Juice during Ultraviolet Processing and Storage

Abstract: The present study shows the effect of UV processing on ascorbic acid, a key vitamin found in many fruit juices. Process developers and researchers can use this study as a model for designing experiments to identify factors that influence the stability of vitamin C and other bioactive compounds during UV processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 35 publications
3
65
0
Order By: Relevance
“…Tikekar, Anantheswaran, and La Borde (2011) also demonstrated that UV radiation induced degradation of AA in apple juice using a collimated beam batch UV reactor. They reported that AA degradation occurred more rapidly at higher UV radiation doses.…”
Section: Effect Of Uv On Aa Degradationmentioning
confidence: 95%
“…Tikekar, Anantheswaran, and La Borde (2011) also demonstrated that UV radiation induced degradation of AA in apple juice using a collimated beam batch UV reactor. They reported that AA degradation occurred more rapidly at higher UV radiation doses.…”
Section: Effect Of Uv On Aa Degradationmentioning
confidence: 95%
“…Sricharoen et al [43] examined antioxidant capacity of tomato extract and found that radical scavenging ability of L-ascorbic acid was relatively low, inferior to polyphenols and flavonoids. Moreover, UV irradiation was associated with L-ascorbic acid degradation [44], but considering phenolic compounds are generally more stable, the overall changing trend of antioxidant capacity should be positively related with total phenolic contents.…”
Section: Discussionmentioning
confidence: 99%
“…Rohan et al [12] reported that ascorbic acid degradation was observed in apple juice on exposure to UV radiation. Tran and Farid [13] reported 17 % loss in ascorbic acid after exposure of orange juice to 100 mJ/cm 2 UV radiation.…”
Section: Introductionmentioning
confidence: 98%